Preparation method and application of basic copper nitrate coating for inhibiting zinc dendritic crystal growth
By introducing Cu2NO3(OH)3 into the negative electrode material of zinc ion battery, the problem of overgrowth of dendrites during charging and discharging of zinc batteries is solved, significantly extending the cycle life of the battery and maintaining a high capacity retention rate.
Patent Information
- Application Number
- CN202411461710.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-18
AI Technical Summary
During the charging and discharging process, the deposition behavior of the aqueous zinc ion battery causes excessive growth of dendrites, piercing the separator, causing the battery to fail and reducing the service life of the battery.
Cu2NO3(OH)3 negative electrode material is used to introduce insoluble hydrophobic alkaline copper carbonate into the surface of the zinc electrode to provide rich zinc-philic sites, promote uniform deposition of Zn2+ and reduce the formation of zinc dendrites.
The cycle life of zinc ion batteries has been significantly extended. The cycle life of symmetrical batteries assembled by pure zinc electrodes has reached 1600 hours, stable cycles have been exceeded 400 weeks, and a capacity retention rate of 88.5%.
Smart Images

Figure CN119447147A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an aqueous zinc ion battery negative electrode material, a preparation method and a zinc ion battery, and belongs to the technical field of electrochemical energy. Background Art
[0002] The deposition of Zn during the charge and discharge process of aqueous zinc-ion batteries leads to the "tip effect", which makes the reversibility of aqueous zinc-ion batteries worse, causing excessive growth of dendrites to pierce the diaphragm and cause the battery to fail, greatly reducing the battery life. Therefore, reducing the occurrence of dendrites and side reactions is a crucial factor in the large-scale application of zinc-ion batteries.
[0003] There are many improvement schemes for these side reactions, such as plating Sn on the Zn surface to form alloys, or forming alloys with Cu, Bi, and Al, which provide more nucleation sites while reducing dendrite growth and greatly extending the battery life. Constructing an artificial solid electrolyte interface layer (ASEI) on Zn is also a good way to regulate Zn 2+ Important ways of electroplating chemistry, such as constructing an inorganic salt SEI film NaZnPO4, CaSO4·2H2O, NaTi2(PO4)3, TiO2, BaTiO3 and an organic SEI layer polyacrylonitrile, ZIF-8, covalent organic framework, etc. on the surface of the Zn electrode to inhibit the growth of Zn dendrites and extend the battery life. Or the use of membrane modification, such as fixing copper nanowires on the glass fiber membrane by filtration, is beneficial to Zn 2+ The uniform distribution of flux, at the same time, the nanoscale size makes the Cu nanowires have a large specific surface area, which is beneficial to reduce the local current density and make the Zn 2+ The concentration field is homogenized, thereby inhibiting the growth of zinc dendrites. As a convenient and quick method, electrolyte additives are also widely studied, such as inorganic salt additives NH4F, LiCl, Sc 3+ and PbO etc. act as shields by adsorbing cations onto the surface of Zn sheets, thus inhibiting dendrite growth. Organic electrolyte additives, such as 6-bromo-1H-benzimidazole, histidine, trimethyl phosphate and dodecyltrimethylammonium chloride, etc., can regulate the Zn 2+ The solvation structure reduces the number of water molecules in the solvation sheath, thereby inhibiting byproducts and reducing hydrogen evolution to extend battery life. Some of these additives are heavy metal salts, which will have a certain impact on the environment, and some organic additives will cause certain harm to the human body.
[0004] Interface modification is also an effective method to inhibit side reactions and reduce dendrite growth. For example, a layer of dense NaZnPO4 is electrodeposited on the zinc surface to isolate it from direct contact with the electrolyte and effectively reduce the occurrence of side reactions. However, most of the current interface reactions are relatively cumbersome and complicated. Therefore, a simple and inexpensive zinc electrode coating preparation process is an important condition for its application. Summary of the invention
[0005] The main purpose of the present invention is to provide a negative electrode material for an aqueous zinc ion battery, thereby reducing hydrogen evolution, Zn sheet corrosion and the generation of by-products, and making up for the shortcomings of the prior art.
[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme: S1: Weigh zinc salt and 2-methylimidazole separately, mix them in deionized water, stir at room temperature, and obtain ZIF-8 powder by centrifugation, washing and drying.
[0007] S2: The dried precursor powder and copper salt are stirred at a mass ratio of 14:1 at 40-90°C for 6-24 h, and CNO powder is obtained by centrifugation, washing and drying.
[0008] S3: The obtained CNO powder and polyvinylidene fluoride (PVDF) were mixed in a certain proportion with N-methylpyrrolidone (NMP) as solvent in a mortar, fully ground, and then coated on the surface of Zn foil with a thickness of 5-20 μm, and dried at 40-80°C for 6-24h to obtain the CNO@Zn negative electrode.
[0009] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The raw material cost used in the present invention is low, and the coprecipitation and coating method is simple to operate.
[0010] (2) The Cu2NO3(OH)3 negative electrode of the present invention introduces insoluble hydrophobic basic copper carbonate into the surface of the zinc electrode, providing abundant zinc-philic sites, making Zn 2+ Uniform deposition reduces the formation of zinc dendrites, making the assembled symmetrical battery with pure zinc electrode (cycle life 60 h) have excellent cycle stability and can have a cycle life of 1600 h.
[0011] (3) The Cu2NO3(OH)3 negative electrode of the present invention reduces the direct contact between the electrolyte and the zinc sheet through its strong hydrophobicity, effectively reducing hydrogen evolution, corrosion and the formation of Zn4(OH)6SO4·xH2O byproducts, so that the full-battery aqueous Al-MnO2 button cell assembled with Al-MnO2 has a capacity retention rate of 88.5% compared with bare zinc, and can be stably cycled for more than 400 cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is the X-ray diffraction pattern of the Cu2NO3(OH)3 powder prepared in Example 1.
[0013] Figure 2 This is a scanning electron microscope image of Cu2NO3(OH)3@Zn prepared in Example 1.
[0014] Figure 3 This is the contact angle diagram of Cu2NO3(OH)3@Zn prepared in Example 1 and bare Zn in 2 mol / L ZnSO4 electrolyte after 4 minutes.
[0015] Figure 4 When the Cu2NO3(OH)3@Zn prepared in Example 1 is used as the negative electrode of an aqueous zinc ion battery, the current density is 1 mA / cm 2 , with a surface capacity of 0.5 mAh / cm 2 Below is the charge and discharge performance curve of a symmetrical battery.
[0016] Figure 5 When the Cu2NO3(OH)3@Zn prepared in Example 1 is used as the negative electrode of an aqueous zinc ion battery, the current density is 5 mA / cm 2 , with an area capacity of 1 mAh / cm 2 Below is the charge and discharge performance curve of a symmetrical battery.
[0017] Figure 6 The half-cell assembled with Cu2NO3(OH)3@Zn prepared in Example 1 as the negative electrode material and Cu foil as the positive electrode material was operated at a current density of 2 mA / cm 2 , with a surface capacity of 0.5 mAh / cm 2 Coulomb efficiency diagram below.
[0018] Figure 7 The charge and discharge performance curve of a full battery assembled with Cu2NO3(OH)3@Zn prepared in Example 1 as the negative electrode material and Al-MnO2 as the positive electrode at a current density of 0.5 A / g.
[0019] Figure 8 The charge and discharge performance curve of a full battery assembled with Cu2NO3(OH)3@Zn prepared in Example 1 as the negative electrode material and Al-MnO2 as the positive electrode at a current density of 1 A / g. DETAILED DESCRIPTION
[0020] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0021] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0022] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0023] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0024] Example 1 The basic copper nitrate coating for inhibiting zinc dendrite growth of the present invention comprises the following steps: (1) Zinc nitrate hexahydrate and 2-methylimidazole in a molar ratio of 12:96 were weighed and dissolved in deionized water and stirred at room temperature for 4 h. The precursor ZIF-8 powder was obtained by centrifugation, washing, and drying.
[0025] (2) The dried precursor (M ZIF-8 :229.6 mol g -1 ) The precursor powder and copper salt were stirred at 60 °C for 12 h in a molar ratio of 1:2, and CNO powder was obtained by centrifugation, washing and drying.
[0026] (3) The obtained CNO powder was mixed with polyvinylidene fluoride (PVDF) in a mass ratio of 9:1 using N-methylpyrrolidone (NMP) as solvent in a mortar, ground thoroughly, and then coated on the surface of Zn foil with a thickness of 5 μm. The mixture was dried at 60 °C for 12 h to obtain the Cu2NO3(OH)3@Zn negative electrode.
[0027] The Cu2NO3(OH)3@Zn prepared in this example is denoted as CNO@Zn and used as the positive and negative electrodes of a button battery. A glass fiber separator and 2 mol / L ZnSO4 are used as the electrolyte. The button battery is assembled under normal conditions and is denoted as a CNO@Zn / / CNO@Zn symmetrical battery.
[0028] The Cu2NO3(OH)3@Zn prepared in this example is denoted as CNO@Zn and used as the negative electrode of a button cell. Copper foil is used as the positive electrode. A glass fiber separator is used. 2 mol / L ZnSO4 is used as the electrolyte. The button cell is assembled under normal conditions and denoted as CNO@Zn / / Cu half-cell.
[0029] The Cu2NO3(OH)3@Zn prepared in this example is denoted as CNO@Zn and used as the negative electrode of a button cell. Al-MnO2 is used as the positive electrode. A glass fiber separator is used. 2 mol / L ZnSO4 and 0.2 mol / L MnSO4 are used as electrolytes. The button cells are assembled under normal conditions and are denoted as CNO@Zn / / Al-MnO2 full cells.
[0030] Comparative Example 1 Zinc foil is used as the positive and negative electrodes of the button battery, a glass fiber separator is used, and 2 mol / L ZnSO4 is used as the electrolyte. The button battery is assembled under normal conditions and is recorded as a Zn / / Zn symmetric battery.
[0031] Zinc foil is used as the negative electrode of the button battery, copper foil is used as the positive electrode, a glass fiber separator is used, and 2 mol / L ZnSO4 is used as the electrolyte. The button battery is assembled under normal conditions and is denoted as a Zn / / Cu half-cell.
[0032] Zinc foil is used as the negative electrode of the button battery, Al-MnO2 is used as the positive electrode, a glass fiber separator is used, 2 mol / L ZnSO4 and 0.2 mol / L MnSO4 are used as the electrolyte, and the button battery is assembled under normal conditions, which is denoted as Zn / / Al-MnO2 full battery.
[0033] The obtained basic copper nitrate coating was subjected to X-ray diffraction analysis, scanning electron microscopy analysis, contact angle test, symmetric battery cycle life test, half-cell coulomb efficiency test, full battery life and retention rate test, and the results are as follows: Figure 1-Figure 8 shown.
[0034] Figure 1 Shown is the X-ray diffraction of the Cu2NO3(OH)3@Zn sample prepared in Example 1. From the figure, it can be seen that the diffraction peaks of basic copper nitrate can be well observed, indicating that the basic copper nitrate sample was successfully prepared. Figure 2 This is a scanning electron microscope image of the sample, in which it can be seen that basic copper nitrate nanosheets with an average particle size of 0.5-1 micron are evenly distributed on the surface of the zinc foil. Figure 3 Contact angle test of Cu2NO3(OH)3@Zn sample after 4 minutes in 2 mol / L ZnSO4 electrolyte.
[0035] Figure 4 and Figure 5 The symmetrical battery constant current charge and discharge test diagrams of the symmetrical battery assembled in Example 1 and Comparative Example 1 at low current and high current density are shown respectively. Figure 4 It can be seen that the symmetrical battery has a current density of 1 mA / cm 2 , with a surface capacity of 0.5 mAh / cm 2 Under the conditions of CNO@Zn overpotential is significantly smaller than that of the symmetric battery with pure Zn electrode, indicating that the presence of the basic copper nitrate coating reduces the nucleation barrier of Zn and also reduces the polarization, promoting a relatively uniform zinc deposition / dissolution process, so that the symmetric battery with basic copper nitrate coating has a cycle life of 1600 h compared with the 60 h cycle life of the pure zinc symmetric battery. Figure 5 5 mA / cm 2 The high current density of 1 mAh / cm 2 This rule also applies to surface capacity, and the battery has a longer cycle life than pure Zn electrode, indicating that the presence of basic copper nitrate can effectively reduce the occurrence of side reactions and thus extend battery life.
[0036] Figure 6 The half-cell assembled with Example 1 and Comparative Example 1 as the negative electrode of the button battery and Cu foil as the positive electrode of the button battery at 2 mA / cm 2 Coulombic efficiency tested under current density. It can be seen from the figure that due to a series of side reactions, the coulombic efficiency of the pure Zn electrode fluctuates greatly after 190 cycles, resulting in battery damage. However, the half-cell of the basic copper carbonate coating prepared in Example 1 can still maintain a coulombic efficiency of 99.8% after 1600 cycles, which is significantly better than that of Comparative Example 1 due to the excellent ability of basic copper carbonate to inhibit side reactions.
[0037] Figure 7 and Figure 8 The figures are respectively the charge and discharge test graphs of the full battery assembled with Example 1 and Comparative Example 1 as the negative electrode sheets of the button battery and Al-MnO2 as the positive electrode sheet of the button battery at different current densities. Figure 7 This is a charge and discharge test diagram at a current density of 0.5 A / g. From the figure, it can be seen that the initial capacity of the Zn / / Al-MnO2 battery is the same as the initial capacity of the CNO@Zn / / Al-MnO2. The pure Zn electrode rapidly decays its battery capacity after 140 cycles due to various side reactions. The CNO@Zn / / Al-MnO2 full battery in Example 1 still has a capacity retention rate of 88.5% after 400 cycles due to the reduction of side reactions. Figure 8This is a charge and discharge test diagram at a current density of 1 A / g. From the figure, it can be seen that the Zn / / Al-MnO2 battery has a rapid capacity decay and finally fails after 900 cycles due to a series of side reactions. The CNO@Zn / / Al-MnO2 battery prepared in Example 1 can be stably cycled for 1400 cycles and the retention rate is maintained at 93.4% because the side reactions are suppressed, which is significantly better than Comparative Example 1.
[0038] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions claimed to be protected by the present invention.
Claims
1. A method for preparing a basic copper nitrate coating for inhibiting zinc dendrite growth, characterized in that: The steps include: S1: zinc salt and 2-methylimidazole are mixed and stirred at room temperature for reaction, and the reaction product is centrifuged, washed, and dried to obtain ZIF-8 precursor powder; S2: Stirring ZIF-8 precursor powder and copper salt in a certain ratio at a certain temperature for a certain time, centrifuging, washing and drying to obtain CNO powder; S3: The obtained CNO powder and polyvinylidene fluoride are fully ground in a solvent, and then coated on the surface of Zn foil. After drying, a basic copper nitrate coating Cu2NO3(OH)3@Zn is obtained to inhibit the growth of zinc dendrites.
2. The method for preparing a basic copper nitrate coating for inhibiting zinc dendrite growth according to claim 1, characterized in that: The zinc salt is any one of zinc oxide, zinc sulfate heptahydrate, zinc nitrate hexahydrate and zinc chloride.
3. The method for preparing a basic copper nitrate coating for inhibiting zinc dendrite growth according to claim 1, characterized in that: The copper salt described in S2 is one of copper acetate, copper nitrate, copper sulfate and copper chloride.
4. The method for preparing a basic copper nitrate coating for inhibiting zinc dendrite growth according to claim 1, characterized in that: The temperature in S2 is 40-90°C and the stirring time is 6-24 h.
5. The method for preparing a basic copper nitrate coating for inhibiting zinc dendrite growth according to claim 1, characterized in that: The coating thickness in S3 is 5-20 μm.
6. A method for preparing a basic copper nitrate coating for inhibiting zinc dendrite growth, characterized in that: The Cu2NO3(OH)3@Zn prepared according to the method according to any one of claims 1 to 5 has XRD peaks at characteristic peak positions at about 12.8°, 21.58°, 25.77°, and 33.51° 2θ.
7. A negative electrode or positive electrode material, characterized in that: The negative electrode or positive electrode material includes the basic copper nitrate coating for inhibiting zinc dendrite growth as described in claim 6.
8. A symmetrical battery, characterized in that: The positive electrode sheet and / or the negative electrode sheet of the symmetrical battery adopts the basic copper nitrate coating for inhibiting the growth of zinc dendrites as claimed in claim 6.
9. A half-cell, characterized in that: The negative electrode plate of the half-cell adopts the basic copper nitrate coating for inhibiting the growth of zinc dendrites as claimed in claim 6.
10. A full battery, characterized in that: The negative electrode plate of the full battery adopts the basic copper nitrate coating for inhibiting the growth of zinc dendrites as described in claim 6.
Citation Information
Patent Citations
Double-function protective layer modified zinc negative electrode and preparation method thereof
CN115064651A
Monoatomic dispersed Cu and Zn co-doped carbon sheet flexible material as well as preparation method and application thereof
CN117488543A
Wide-temperature-range aqueous zinc ion hybrid supercapacitor based on metal organic framework material
CN118116747A